On the way to the wedding - Quinn, Julia (New York : Avon Books, 2006)
This is the final volume in the historical fiction series set in Regency England. This one follows the youngest son, Gregory, as he thinks he falls in love?, couldn't possible be in love? and finally is truly in love.
Keywords: Regency fiction; Historical fiction; Love stories